Antiferromagnetic fluctuations and charge carrier localization in ferromagnetic bilayer manganites: electrical resistivity scales exponentially with short-range order controlled by temperature and magnetic field. (18th June 2020) - Perring, T G; Adroja, D T; Champion, J D M; Aeppli, G; Chaboussant, G; Kimura, T; Tokura, Y; Manuel, P
Abstract: The compound La2−2 x Sr1+2 x Mn2 O7, x = 0.30–0.40, consists of bilayers of ferromagnetic metallic MnO2 sheets that are separated by insulating layers. The materials show colossal magnetoresistance—a reduction in resistivity of up to two orders of magnitude in a field of 7 T—at their three-dimensional ordering temperatures, T C = 90–126 K, and are the layered analogues of the widely studied pseudo-cubic perovskite manganites, R1− x A x MnO3 (R = rare earth, A = Ca, Sr, Ba, Pb). Two distinct short-range orderings—antiferromagnetic fluctuations and correlated polarons, which are related to the magnetic and the lattice degrees of freedom respectively—have previously been discovered in La2−2 x Sr1+2 x Mn2 O7, x = 0.40, and have each been qualitatively connected to the resistivity. Here, in a comprehensive study as a function of both temperature and magnetic field for the different hole-concentrations per Mn site of x = 0.30 and 0.35, we show that antiferromagnetic fluctuations also appear at temperatures just above T C, and that the intensities of both the antiferromagnetic fluctuations and polaron correlations closely track the resistivity. In particular, for x = 0.35 we show that there is a simple scaling relation between the intensities of the antiferromagnetic fluctuations and the in-plane resistivity that applies for the temperatures and magnetic fields used in the experiments. The results show that antiferromagnetic fluctuations are a common feature of La2−2 x Sr1+2 x Mn2 O7 with ferromagnetic bilayers, and that there is a close connection between the antiferromagnetic fluctuations and polarons in these materials.